A gestão no Campus Universitário de Bragança no período de pandemia da COVID-19: desafios e possibilidades - SILVA, Jordana Melo da (2023)
The present work focuses on the management at the Bragança University Campus during the COVID-19 pandemic, exploring the challenges faced and the possibilities that arose in this context. The pandemic posed an unprecedented challenge for higher education institutions, requiring the adoption of emergency measures and the reconfiguration of management practices. The aim of this study is to analyze how the management of the Bragança University Campus adapted to and confronted the challenges posed by the pandemic, seeking to identify the strategies employed and the possibilities that emerged during this period. The research is based on a qualitative approach, using interviews with managers and faculty members as the main sources of data. An important part of the research is dedicated to analyzing the strategies adopted by the campus management to overcome challenges and explore possibilities that arose during the pandemic. Actions such as the establishment of working groups for planning and monitoring activities, providing training for faculty members in the use of educational technologies, implementing psychosocial support systems for students, and promoting solidarity and community engagement initiatives are identified. Finally, the study concludes that the management of the Bragança University Campus faced significant challenges during the pandemic but found possibilities for innovation and transformation. The rapid and efficient adaptation to new demands, the pursuit of creative solutions, and the concern for the well- being of the academic community were key elements in this process. The research highlights the importance of continuously improving management and developing strategies that enable more resilient and prepared responses to future challenges.